2014
DOI: 10.1016/j.molcel.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hsp90 N Domain SUMOylation Recruits Aha1 and ATP-Competitive Inhibitors

Abstract: Summary The stability and activity of numerous signaling proteins in both normal and cancer cells depends on the dimeric molecular chaperone Heat Shock Protein 90 (Hsp90). Hsp90 function is coupled to ATP binding and hydrolysis, and requires a series of conformational changes that are regulated by co-chaperones and numerous posttranslational modifications (PTMs). SUMOylation is one of the least understood Hsp90 PTMs. Here we show that asymmetric SUMOylation of a conserved lysine residue in the N-domain of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
102
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 57 publications
7
102
0
2
Order By: Relevance
“…Therefore, our results support previous findings showing that asymmetry plays an important role in homodimeric Hsp90 systems: asymmetry is required for client binding 39 , asymmetric SUMOylation facilitates cochaperone binding 40 , nucleotide affinity is asymmetric 22 and hydrolysis is only required in one subunit 41,42 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our results support previous findings showing that asymmetry plays an important role in homodimeric Hsp90 systems: asymmetry is required for client binding 39 , asymmetric SUMOylation facilitates cochaperone binding 40 , nucleotide affinity is asymmetric 22 and hydrolysis is only required in one subunit 41,42 .…”
Section: Discussionsupporting
confidence: 92%
“…Mollapour et al (33) have reported that diminished Hsp90/ Aha1 interaction associated with reduced ATPase stimulation has little effect on the activation of some client proteins, pointing to an additional role of Aha1 beyond Hsp90 ATPase activation. In line with this suggestion is our finding that the majority of Aha1 in mammalian cells and tissues is self-contained and independent of Hsp90 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cancer cells to exploit HSP90 for two purposes including maintenance of activated onco-proteins and buffer the stress induced by malignant lifestyle (Neckers and Workman 2012). The action mechanism of these drugs was not known before Mollapour et al, (2014), who uncovered the role of asymetric SUMOylation of N domain of both yeast K178 and human K191 facilitates the recruitment of ATPase activating cochaperone Aha1 and binding of HSP90 to inhibitors (Mollapour et al, 2014). This indicates that an increased HSP90 SUMOylation sensitizes yeast and mammalian cells to HSP90 providing a mechanism of cancer cells sensitivity to these drugs (Mollapour, et al, 2014).…”
Section: Sumoylation and Anticancer Drugsmentioning
confidence: 99%
“…The action mechanism of these drugs was not known before Mollapour et al, (2014), who uncovered the role of asymetric SUMOylation of N domain of both yeast K178 and human K191 facilitates the recruitment of ATPase activating cochaperone Aha1 and binding of HSP90 to inhibitors (Mollapour et al, 2014). This indicates that an increased HSP90 SUMOylation sensitizes yeast and mammalian cells to HSP90 providing a mechanism of cancer cells sensitivity to these drugs (Mollapour, et al, 2014).Autophagy, an important process of homeostasis maintenance, by which organisms remove harmful aggregates by a cytosolic cargo system to lysosomes (Dikic et al, 2010), the dysfunction of which causes certain neurological disorders and cancers (Levine and Kroemer, 2008;Rubinsztein, 2006). The findings of specific Ub binding receptors responsible for selective autophagy and the SUMOylation of autophagy-specific Ub like modifiers LC3/GABARAP provides a link between ubiquitinproteasome system (UPS) and autophagy, hence provides selective autophagy as another means to remove harmful proteins that might causes cancers including multiple myeloma (Hoang et al, 2009).…”
mentioning
confidence: 99%